THE EFFECT OF UV LIGHT ON THE YIELD AND CHARACTERISTICS OF BIODIESEL FROM CANDLENUT OIL USING A TiO2-K2O/NATURAL ZEOLITE COMPOSITE - Muhammad Triyogo Adiwibowo; Indar Kustiningsih; Alia Badra Pitaloka; Wardalia Wardalia; Tati Jumiarti; Hani Mulyani (JURNAL INTEGRASI PROSES, 2023)
This study examines the effect of UV irradiation on the yield and physical characteristics of biodiesel from candlenut oil using a TiO2-K2O/natural zeolite composite. Natural zeolite was activated with KOH and impregnated with TiO2. The formed composite was analyzed with an X-ray diffractometer. Biodiesel was synthesized with candlenut oil to methanol molar ratio and catalyst loading (w/w oil) 1:4, 1:6, 1:8, and 2, 4, and 6%, respectively. The XRD analysis shows peak patterns of anatase and rutile TiO2, K2O, and zeolite. UV light can increase biodiesel yield, with the highest yield at 82.08% at oil to methanol molar ratio of 1:8 and a catalyst loading of 2%. The physical properties of biodiesel are in accordance with national standard SNI 7182:2015. GCMS results shows that the main components of fatty acid methyl ester from biodiesel are methyl oleate, methyl palmitate, and methyl linoleate.